High-toughness high-wear-resistance Ti (C, N)-based metal ceramic material and preparation method thereof
By depositing a transition layer and a TiAlN/ZrN functional layer on the cermet matrix, the problem of insufficient strength, toughness and wear resistance of cermet tools in titanium alloy processing is solved, and the preparation of high-strength, tough and wear-resistant Ti(C,N)-based cermet materials is realized, which is suitable for titanium alloy cutting.
Patent Information
- Application Number
- CN202411875392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
During the processing of titanium alloy, metal cermet tools have problems such as insufficient strength and toughness and poor wear resistance, which affect the tool life and workpiece surface quality.
A tri-crystal cermet matrix is prepared by multi-scale Ti(C,N) atomized powder, and a transition layer and a TiAlN/ZrN soft and hard alternating functional layer are deposited by a continuous progressive negative bias to form a high-strength, tough and wear-resistant Ti(C,N)-based cermet material.
It improves the bonding strength between the coating and the cermet matrix, has high wear resistance and high hardness on the surface, and has high fracture toughness and high strength on the inside, which is suitable for titanium alloy cutting.
Smart Images

Figure CN119685762A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coated metal ceramic materials, and in particular to a high-strength, high-toughness and high-wear-resistant Ti(C, N)-based metal ceramic material and a preparation method thereof. Background Art
[0002] Ti(C,N) based cermets are considered to be the most promising materials to replace cemented carbide. The hardness, wear resistance and oxidation resistance of cermets are significantly better than those of cemented carbide. At the same time, cermets have higher fracture toughness than diamond, CBN and ceramic materials. Therefore, cermet tools are considered to be ideal candidate materials for cutting titanium alloys.
[0003] However, the titanium alloy machining process has complex working conditions, high cutting temperature, and severe adhesive wear. Metal ceramic tools still have problems such as insufficient strength and toughness, and poor wear resistance, which seriously affects the tool life and workpiece surface quality during titanium alloy cutting. Therefore, the modification of metal ceramics is of great significance. Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a high-strength, high-toughness and high-wear-resistant Ti(C,N)-based metal ceramic material and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] On the one hand, a method for preparing a high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material is provided, comprising the following steps:
[0007] S1: Preparation of three-crystal metal ceramic matrix;
[0008] S2: Depositing a transition layer on the three-crystal metal ceramic substrate using a continuous progressive negative bias;
[0009] S3: preparing a TiAlN / ZrN soft-hard alternating functional layer on the transition layer to obtain the high-strength, toughness and wear-resistant Ti(C,N)-based metal ceramic material.
[0010] Preferably, in step S1, the three-crystal metal ceramic matrix is made of multi-scale Ti(C,N) atomized powder, which includes, by mass fraction, 10% to 30% of micron-grade Ti(C,N) atomized powder, 30% to 50% of submicron-grade Ti(C,N) atomized powder, and 20% to 40% of nano-grade Ti(C,N) atomized powder.
[0011] Preferably, the particle size of the micron-grade Ti(C,N) atomized powder is 1-3 μm, the particle size of the submicron-grade Ti(C,N) atomized powder is 300 nm-800 nm, and the particle size of the nano-grade Ti(C,N) atomized powder is 50 nm-100 nm.
[0012] Preferably, in step S2, the transition layer includes a TiN transition layer and an AlN transition layer.
[0013] Preferably, the TiN transition layer is disposed between the AlN transition layer and the three-crystal metal ceramic substrate.
[0014] Preferably, in step S2, when the transition layer is deposited by continuous progressive negative bias, cathode arc ion plating is used for deposition.
[0015] Preferably, during deposition, argon and nitrogen are introduced with a gas flow rate of 200 to 600 sccm, the working targets are a cathode arc Ti target and a cathode arc Al target, the target current is 50 to 200 A, the frequency is 20 to 80 KHz, the duty cycle is 20% to 85%, and the deposition time is 10 to 50 min.
[0016] Preferably, in step S3, the TiAlN / ZrN soft-hard alternating functional layer is prepared by cathode arc ion plating, and the modulation ratio of ZrN to TiAlN in the TiAlN / ZrN soft-hard alternating functional layer is 5:1 to 10:1.
[0017] Preferably, when preparing the TiAlN / ZrN soft and hard alternating functional layer, argon and nitrogen are introduced, the gas flow rate is 200-600sccm, the working targets are a cathode arc TiAl target and a cathode arc Zr target, the target current is 50-200A, the frequency is 20-80KHz, the duty cycle is 20%-85%, the substrate bias is -40--100V, and the deposition time is 10-60min.
[0018] On the other hand, a high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material is also provided, which is prepared by any of the above-mentioned preparation methods of the high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material.
[0019] The beneficial effects of the present invention are:
[0020] The present invention uses three-crystal metal ceramic as a substrate, and continuously and progressively bias deposits a transition layer and a TiAlN / ZrN soft-hard alternating functional layer on the three-crystal metal ceramic substrate, so that the coating prepared by the present invention is well combined with the metal ceramic substrate, has high wear resistance and high hardness on the surface, and has high fracture toughness and high strength inside. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 It is a schematic structural diagram of the high-strength, toughness and wear-resistant Ti(C,N)-based metal ceramic material of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0024] On the one hand, if Figure 1 As shown, the present invention provides a method for preparing a high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material, comprising the following steps:
[0025] S1: Preparation of three-crystal metal ceramic matrix.
[0026] In a specific embodiment, the three-crystal metal ceramic matrix is made of multi-scale Ti (C, N) atomized powder, which includes 10% to 30% of micron-grade Ti (C, N) atomized powder, 30% to 50% of submicron-grade Ti (C, N) atomized powder, and 20% to 40% of nano-grade Ti (C, N) atomized powder by mass fraction. Optionally, the particle size of the micron-grade Ti (C, N) atomized powder is 1 to 3 μm, the particle size of the submicron-grade Ti (C, N) atomized powder is 300nm to 800nm, and the particle size of the nano-grade Ti (C, N) atomized powder is 50nm to 100nm.
[0027] In the above embodiment, the present invention uses multi-scale Ti(C,N) atomized powder including nano-scale, submicron-scale and micron-scale, which can use nano-crystals to strengthen and harden, micro-crystals to toughen, submicron-crystals to strengthen, toughen and harden, and at the same time help the gradient transition of nano-crystals and micro-crystals in scale direction.
[0028] In a specific embodiment, the three-crystal metal ceramic matrix is made of multi-scale Ti (C, N) atomized powder, submicron TaC, Mo2C, WC, Co, Ni commercial powder. Specifically, each powder is mixed according to a ratio (the total mass fraction of multi-scale Ti (C, N) atomized powder is 50% to 70%, the mass fraction of TaC, Mo2C and WC is 10% to 30%, and the mass fraction of Co and Ni is 10% to 30%), ball milled and dried, sieved, added with a molding agent, molded, and pressure sintered to obtain the three-crystal metal ceramic matrix.
[0029] Optionally, the ball milling time is 40 to 80 hours, the ball milling medium is gasoline or alcohol, the mesh size of the sieve is 40 to 100 mesh, and the molding agent is paraffin or rubber. The press pressure is 40MPa to 200MPa, and the size of the pressed green sheet is a length of 6.5×5.25×20mm. Sintering is carried out in an argon or nitrogen atmosphere, the heating rate is 5℃ / min to 20℃ / min, the sintering temperature is 1300 to 1550℃, the holding time is 1 to 3 hours, and then the three-crystal metal ceramic matrix is obtained by cooling with the furnace.
[0030] S2: Depositing a transition layer on the three-crystal metal ceramic substrate using a continuous progressive negative bias.
[0031] In a specific embodiment, the transition layer includes a TiN transition layer and an AlN transition layer. Optionally, the TiN transition layer is disposed between the AlN transition layer and the three-crystal metal ceramic substrate.
[0032] In a specific embodiment, when the transition layer is deposited by continuous progressive negative bias, cathode arc ion plating is used for deposition. Optionally, during deposition, argon and nitrogen are introduced, the gas flow rate is 200-600 sccm, the working target is a cathode arc Ti target and a cathode arc Al target, the target current is 50-200A, the frequency is 20-80KHz, the duty cycle is 20%-85%, and the deposition time is 10-50min.
[0033] In the above embodiment, a transition layer is deposited by a continuous progressive negative bias, and the ion energy is continuously changed and deposited on the metal ceramic. Compared with a gradient bias or a constant bias, it has a coating structure with a more continuous transition, and the coating has the characteristics of low stress and high bonding strength.
[0034] In a specific embodiment, before depositing the transition layer, the three-crystal metal ceramic substrate is further subjected to grinding, polishing and cleaning. Optionally, the three-crystal metal ceramic substrate is ground with a diamond wheel, polished with a grinding paste, cleaned with ethanol or acetone ultrasonic wave, and then sandblasted and dried.
[0035] In a specific embodiment, depositing a transition layer on the three-crystal metal ceramic substrate using a continuous progressive negative bias voltage specifically includes the following steps:
[0036] The cleaned three-crystal metal ceramic substrate is loaded into the coating furnace, and the distance between the substrate and the cathode target is 10mm to 60mm. Vacuum to 1 to 5×10 -3 MPa, argon ion etching substrate surface, etching time is 30 ~ 80min. TiN and AlN transition layers are deposited on the surface of the three-crystal metal ceramic substrate. The coating deposition method is: at a temperature of 300℃ ~ 450℃, a nitrogen flow rate of 200 ~ 400sccm, and an argon flow rate of 200 ~ 400sccm. Connect Ti 99.9 and Al 99.9 Arc target, turn on the substrate bias power supply, the bias is continuous progressive, where -U / T = 4. The deposition time is 10 to 50 minutes.
[0037] S3: preparing a TiAlN / ZrN soft-hard alternating functional layer on the transition layer to obtain the high-strength, toughness and wear-resistant Ti(C,N)-based metal ceramic material.
[0038] In the present invention, by providing the TiAlN / ZrN soft-hard alternating functional layer, the coating can be endowed with both wear resistance and friction reduction capabilities, and is more suitable for titanium alloy cutting.
[0039] In a specific embodiment, the TiAlN / ZrN soft-hard alternating functional layer is prepared by cathode arc ion plating, and the modulation ratio of ZrN to TiAlN of the TiAlN / ZrN soft-hard alternating functional layer is 5:1 to 10:1. Optionally, when preparing the TiAlN / ZrN soft-hard alternating functional layer, argon and nitrogen are introduced, the gas flow rate is 200 to 600 sccm, the working target is a cathode arc TiAl target and a cathode arc Zr target, the target current is 50 to 200A, the frequency is 20 to 80KHz, the duty cycle is 20% to 85%, the substrate bias is -40 to -100V, and the deposition time is 10 to 60min.
[0040] Optionally, in the above embodiment, when preparing the TiAlN / ZrN soft-hard alternating functional layer, the substrate support is rotated at a speed of 3 rpm to 5 rpm.
[0041] On the other hand, a high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material is also provided, which is prepared by any of the above-mentioned preparation methods of the high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material.
[0042] Example 1
[0043] A high-strength, high-toughness, high-wear-resistant Ti(C,N)-based cermet material is prepared by the following steps:
[0044] (1) Preparing a three-crystal metal ceramic substrate and pretreating the three-crystal metal ceramic substrate
[0045] 15wt% 2μm, 30wt% 500nm and 23wt% 100nm Ti (C, N) powders were weighed in proportion, 3wt% TaC, 3wt% Mo2C, 10wt% WC, 8wt% Co and 8wt% Ni micron powders were added, the powders were mixed in proportion, aviation gasoline and paraffin were added, and ball milled for 48h. After ball milling, the mixture was sieved and dried, and granulated using a 60-mesh screen. The mixture was molded under a pressure of 100MPa in a press to form a strength bar with a size of 6.5×5.25×20mm. Then the green body was placed in an atmosphere sintering furnace, argon was introduced, the heating rate was 10℃ / min, the sintering temperature was 1450℃, the insulation time was 1h, and then cooled with the furnace to obtain a three-crystal metal ceramic matrix. The three-crystal metal ceramic matrix was mechanically ground, polished, ultrasonically cleaned and dried.
[0046] (2) Depositing a transition layer and a TiAlN / ZrN soft-hard alternating functional layer on the three-crystal metal ceramic substrate
[0047] The pretreated three-crystal metal ceramic substrate was placed in the coating furnace and vacuumed to 5×10 -3 Pa. The distance between the substrate and the target is 6 cm. Argon gas is introduced with a gas flow rate of 220 sccm. The substrate is heated to 350°C and the bias voltage is set to -250 V. Ar + Etching 10min. 1 Ti 99 The target is powered on, and the target current is 180A. The substrate bias is set to -800V, using high energy Ti + The substrate was etched for 20 minutes. The bias voltage was set to continuous progressive mode, 250 sccm of nitrogen was introduced, and the TiN coating was deposited for 20 minutes. Then the Ti 99 Target, open an Al 99 Target, Al target current 180A, AlN coating deposition 10min. Turn off the continuous bias, set the bias to constant bias, substrate bias to -60V. At the same time, turn on the Ti 99 Target, Al 99 Target, Zr 99 The target and the substrate support rotate at a speed of 5 rpm, and TiAlN / ZrN soft and hard alternating layers are deposited for 60 minutes, thereby obtaining the high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material of the present invention.
[0048] The three-crystal metal ceramic matrix of this embodiment has high hardness and fracture toughness, and the hardness is 1610kgf·mm-2 , strength is 1882MPa, toughness is 9.89MPa·m 1 / 2 The coating is well bonded to the substrate, and the nano-hardness of the coating is 26±0.65GPa.
[0049] Example 2
[0050] A high-strength, high-toughness, high-wear-resistant Ti(C,N)-based cermet material is prepared by the following steps:
[0051] (1) Preparing a three-crystal metal ceramic substrate and pretreating the three-crystal metal ceramic substrate
[0052] 23wt% 2μm, 30wt% 500nm and 15wt% 100nm Ti (C, N) powders were weighed in proportion, 3wt% TaC, 3wt% Mo2C, 10wt% WC, 8wt% Co and 8wt% Ni micron powders were added, the powders were mixed in proportion, aviation gasoline and paraffin were added, and the powders were ball milled for 72h. After ball milling, the mixture was sieved and dried, and granulated using a 60-mesh screen. The mixture was molded under a pressure of 100MPa in a press to form a strength bar with a size of 6.5×5.25×20mm. Then the green body was placed in an atmosphere sintering furnace, argon was introduced, the heating rate was 10℃ / min, the sintering temperature was 1480℃, the insulation time was 1h, and then cooled with the furnace to obtain a three-crystal metal ceramic matrix. The three-crystal metal ceramic matrix was mechanically ground, polished, ultrasonically cleaned and dried.
[0053] (2) Depositing a transition layer and a TiAlN / ZrN soft-hard alternating functional layer on the three-crystal metal ceramic substrate
[0054] The pretreated three-crystal metal ceramic substrate was placed in a coating furnace and vacuumed to 3×10 -3 Pa. The distance between the substrate and the target is 4 cm. Argon gas is introduced with a gas flow rate of 220 sccm. The substrate is heated to 350°C and the bias voltage is set to -250 V. Ar + Etching 15min. 1 Ti 99 The target is powered on, and the target current is 180A. The substrate bias is set to -800V, using high energy Ti + The substrate was etched for 25 minutes. The bias voltage was set to continuous progressive mode, 250 sccm of nitrogen was introduced, and the TiN coating was deposited for 20 minutes. Then the Ti 99 Target, open an Al 99 Target, Al target current 180A, AlN coating deposition 20min. Turn off the continuous bias, set the bias to constant bias, substrate bias to -60V. At the same time, turn on the Ti 99 Target, Al 99 Target, Zr 99The target and the substrate support rotate at a speed of 5 rpm, and TiAlN / ZrN soft and hard alternating layers are deposited for 60 minutes, thereby obtaining the high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material of the present invention.
[0055] The three-crystal metal ceramic matrix of this embodiment has high hardness and fracture toughness, and the hardness is 1550kgf·mm -2 , strength is 1802MPa, toughness is 10.13MPa·m 1 / 2 The coating is well bonded to the substrate, and the nanohardness of the coating is 24±0.76GPa.
[0056] Example 3
[0057] A high-strength, high-toughness, high-wear-resistant Ti(C,N)-based cermet material is prepared by the following steps:
[0058] (1) Preparing a three-crystal metal ceramic substrate and pretreating the three-crystal metal ceramic substrate
[0059] 9wt% 2μm, 50wt% 500nm and 9wt% 100nm Ti (C, N) powders were weighed in proportion, 3wt% TaC, 3wt% Mo2C, 10wt% WC, 8wt% Co and 8wt% Ni micron powders were added, the powders were mixed in proportion, aviation gasoline and paraffin were added, and ball milled for 36h. After ball milling, the mixture was sieved and dried, and granulated using a 60-mesh screen. The mixture was molded under a pressure of 100MPa in a press to form a strength bar with a size of 6.5×5.25×20mm. Then the green body was placed in an atmosphere sintering furnace, argon was introduced, the heating rate was 10℃ / min, the sintering temperature was 1460℃, the insulation time was 1h, and then cooled with the furnace to obtain a three-crystal metal ceramic matrix. The three-crystal metal ceramic matrix was mechanically ground, polished, ultrasonically cleaned and dried.
[0060] (2) Depositing a transition layer and a TiAlN / ZrN soft-hard alternating functional layer on the three-crystal metal ceramic substrate
[0061] The pretreated three-crystal metal ceramic substrate was placed in a coating furnace and vacuumed to 3×10 -3 Pa. The distance between the substrate and the target is 5 cm. Argon gas is introduced with a gas flow rate of 240 sccm. The substrate is heated to 350°C and the bias voltage is set to -300 V. Ar + Etching 15min. 1 Ti 99 The target is powered on, and the target current is 180A. The substrate bias is set to -800V, using high energy Ti + The substrate was etched for 30 minutes. The bias voltage was set to continuous progressive mode, 260 sccm of nitrogen was introduced, and the TiN coating was deposited for 20 minutes. Then the Ti 99Target, open an Al 99 Target, Al target current 180A, AlN coating deposition 20min. Turn off the continuous bias, set the bias to constant bias, substrate bias to -60V. At the same time, turn on the Ti 99 Target, Al 99 Target, Zr 99 The target and the substrate support rotate at a speed of 5 rpm, and TiAlN / ZrN soft and hard alternating layers are deposited for 60 minutes, thereby obtaining the high-strength, toughness and wear-resistant Ti(C, N)-based metal ceramic material of the present invention.
[0062] The three-crystal metal ceramic matrix of this embodiment has high hardness and fracture toughness, and the hardness is 1680kgf·mm -2 , strength is 1924MPa, toughness is 10.32MPa·m 1 / 2 The coating is well bonded to the substrate, and the nanohardness of the coating is 27±0.45GPa.
[0063] In summary, the coating prepared by the present invention is well bonded to the metal ceramic substrate, has high wear resistance and high hardness on the surface, and has high fracture toughness and high strength inside. Compared with the prior art, the present invention has significant progress.
[0064] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material, characterized in that: The following steps are involved: S1: Preparation of three-crystal metal ceramic matrix; S2: Depositing a transition layer on the three-crystal metal ceramic substrate using a continuous progressive negative bias; S3: preparing a TiAlN / ZrN soft-hard alternating functional layer on the transition layer to obtain the high-strength, toughness and wear-resistant Ti(C,N)-based metal ceramic material.
2. The method for preparing the high-strength, toughness and wear-resistant Ti(C,N)-based cermet material according to claim 1, characterized in that: In step S1, the three-crystal metal ceramic matrix is made of multi-scale Ti(C,N) atomized powder. In terms of mass fraction, the multi-scale Ti(C,N) atomized powder includes 10% to 30% of micron-grade Ti(C,N) atomized powder, 30% to 50% of submicron-grade Ti(C,N) atomized powder, and 20% to 40% of nano-grade Ti(C,N) atomized powder.
3. The method for preparing the high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material according to claim 2, characterized in that: The particle size of the micron-grade Ti(C, N) atomized powder is 1-3 μm, the particle size of the submicron-grade Ti(C, N) atomized powder is 300 nm-800 nm, and the particle size of the nano-grade Ti(C, N) atomized powder is 50 nm-100 nm.
4. The method for preparing the high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material according to claim 1, characterized in that: In step S2, the transition layer includes a TiN transition layer and an AlN transition layer.
5. The method for preparing the high-strength, toughness and wear-resistant Ti(C,N)-based cermet material according to claim 4, characterized in that: The TiN transition layer is arranged between the AlN transition layer and the three-crystal metal ceramic substrate.
6. The method for preparing the high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material according to claim 1, characterized in that: In step S2, when the transition layer is deposited by continuous progressive negative bias, cathode arc ion plating is used for deposition.
7. The method for preparing the high-strength, high-toughness and high-wear-resistant Ti(C,N)-based cermet material according to claim 6, characterized in that: During deposition, argon and nitrogen are introduced with a gas flow rate of 200-600sccm. The working targets are a cathode arc Ti target and a cathode arc Al target. The target current is 50-200A, the frequency is 20-80KHz, the duty cycle is 20%-85%, and the deposition time is 10-50min.
8. The method for preparing the high-strength, toughness and wear-resistant Ti(C,N)-based cermet material according to claim 1, characterized in that: In step S3, the TiAlN / ZrN soft-hard alternating functional layer is prepared by cathode arc ion plating, and the modulation ratio of ZrN to TiAlN in the TiAlN / ZrN soft-hard alternating functional layer is 5:1 to 10:
1.
9. The method for preparing the high-strength, toughness and wear-resistant Ti(C,N)-based cermet material according to claim 8, characterized in that: When preparing the TiAlN / ZrN soft-hard alternating functional layer, argon and nitrogen are introduced, the gas flow rate is 200-600sccm, the working targets are a cathode arc TiAl target and a cathode arc Zr target, the target current is 50-200A, the frequency is 20-80KHz, the duty cycle is 20%-85%, the substrate bias is -40--100V, and the deposition time is 10-60min.
10. A high-strength, high-toughness, high-wear-resistant Ti(C,N)-based metal ceramic material, characterized in that: The high-strength, high-toughness and high-wear-resistant Ti(C,N)-based metal ceramic material is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Metal ceramic alloy free of core-ring structure and preparation method thereof
CN109338193A
Transition metal nitride coating with nano multilayer structure as well as preparation method and application thereof
CN113416926A
TiCN-based metal ceramic with gradient structure and method for improving coating binding force of TiCN-based metal ceramic
CN113564399A
Metal ceramic cutter and preparation method thereof
CN118513556A
TiAlN / AlTiN / ZrN coated cutting tool with composite multilayer structure and preparation method of TiAlN / AlTiN / ZrN coated cutting tool
CN118957492A